Urban Farming dengan Budidaya Tabulampot Jambu Air di Dusun Bener, Tegalrejo, D.I Yogyakarta - Sri Sari Utami; Endah Ratnaningsih; Yeni Indra Kumalasari; Rahayu Widowati (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
Limited space in the city is a problem in the agricultural sector. Urban farming is one of the strategies undertaken to deal with these problems. Several studies have reported that urban farming is considered to be able to increase food security in urban areas, especially the types of food that can be produced on limited space. The utilization of limited space to develop agriculture has been widely carried out, such as fruit cultivation in pots. This method has several advantages, including easy maintenance, cheap, and can be an alternative to produce healthy food for the family. Community service activities in agriculture and animal husbandry are one of the efforts to develop potential in the community. This activity aims to make people in Bener village, Tegalrejo, Yogyakarta know about urban farming and can apply it in their environment. The implementation of activities includes urban farming socialization and fruit cultivation in pots, planting media preparation, introduction of various varieties of guava fruit, transplanting and maintenance practices. The practice of planting and direct mentoring is effective in attracting people to try to implement urban farming in their environment.